A walking bipedal robot using a position control algorithm based on center of mass criterion - Magsino, Elmer R. (Animo Repository, 2019)
A position control algorithm based on inverse kinematics and a control strategy utilizing the Center of Mass criterion are implemented to yield a walking bipedal robot. The bipedal robot has no upper body, stands approximately 50 cm and weighs about four kg. Each leg of the robot has five degrees of freedom: two at the hip, two at the ankles, and one at the knee. The closed form solution of each joint angle is derived by using inverse kinematics, following the Denavit- Hartenberg guidelines to determine the structural parameters of the biped. Such closed form equations determine the value of the joint angle to achieve an instance needed to complete the walking activity. Bipedal locomotion is verified by both simulation and experiments. Simulation results provide desired joint angle trajectories and will serve as benchmark for the actual experiments. Experimental results show that actual step length, foot clearance and hip height gait parameters do not exceed one centimeter from the target. Also, the joint angle mean square error has a maximum deviation of 11 degrees. © 2006-2019 Asian Research Publishing Network (ARPN).